The use of native pasture species in the rehabilitation of a limestone quarry - Sanna F.; Cuccureddu M.; Nieddu D.; Mozzi G.L.; Porqueddu C. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
In high environmental value areas, the rehabilitation of quarries requires the use of native well-adapted plant material. The use of forage species could perform the dual function of rehabilitation and production, where livestock breeding is a key aspect. With the aim of evaluating the establishment and persistence of a mixture of native pasture species selected by CNR-ISPAAM from Sardinian populations, a trial for the rehabilitation of a limestone quarry located in a Site of Community Importance (SCI) was carried out. The mixture components were: Medicago polymorpha L., Psoralea bituminosa L., Psoralea morisiana (Pignatti & Metlesics) Greuter, Melilotus indica (L.) All., Lolium rigidum Gaudin and Plantago lanceolata L. Moreover, an amount of commercial seeds of Mediterranean origin of Trifolium subterraneum L. and Dactylis glomerata L. was added. The mixture was distributed by hydro seeding in autumn 2011. Two sowing rate, 12 and 21 g m-2 seeds, were compared. The mixture showed an excellent establishment with the dominance of native annual species and a high soil cover rate from spring of the establishment year. The autumn re-establishment of self-reseeding annual species in the second year was excellent and then it has gradually reduced. Perennial species showed a slow establishment, reaching a satisfactory presence only from third year. Similar results in terms of soil covering and persistence for the two seeding treatments were observed.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)